Economic downturn and stress testing European welfare systems - Francesco Figari; Andrea Salvatori; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2010)
As unemployment rises across the European Union (EU) it is important to understand the extent to which the incomes of the new unemployed are protected by tax-benefit systems and to assess the cost pressures on the social protection systems of this increase in unemployment. This paper uses the EU tax-benefit model EUROMOD to explore these issues, comparing effects in five EU countries. It provides evidence on the differing degrees of resilience of the household incomes of the newly unemployed due to the variations in the protection offered by the tax-benefit systems, according to whether unemployment benefit is payable, the household situation of the unemployed person, and across countries.
Keywords: C81; H55; I3; 330; unemployment; European Union; household income; microsimulation; Arbeitslosigkeit; Haushaltseinkommen; Arbeitslosenversicherung; Öffentlicher Transfer; Öffentlicher Haushalt; Simulation; EU-Staaten